The Effect of Management Entrenchment on the Equity Capital in Iran - Somayeh Baratiyan; Mahdi Salehi (Pakistan Journal of Commerce and Social Sciences, 2013)
Managerial Entrenchment means that management control a significant portion of the equity in the firm and his/her actions is inconsistent with maximizing aim of the Institute. This research examined the impact of managerial entrenchment on cost of capital stock by analyzing of changes in levels. The present paper examines the relationship between managerial entrenchment, Systematic risk, rate of sales growth, the ratio of CEO and the cost of capital stock. Thus, 55 listed companies were analyzed during 2006-2010. The results indicate there is a significant relationship between the difference of managerial entrenchment period and cost of capital stock period and also significant relationship exists between rate of long sales growth, the ratio of CEO and the cost of capital stock, whereas, there is not significant relation between systematic risk and cost of capital stock.